2020
DOI: 10.1007/s42770-020-00294-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pyroligneous acid as a therapeutic agent against Salmonella in a simulated gastrointestinal tract of poultry

Abstract: Pyroligneous acid (PA) was evaluated as a potential alternative to therapeutic antibiotics in poultry. Antimicrobial activity of PA was studied at acidic pH (2.0) and neutral pH (7.0) of the liquid against Salmonella enterica and Lactobacillus acidophilus. Acidic PA gave a MIC value of 0.8% (v/v) and 1.6% (v/v), and neutralized PA gave a MIC value of 1.6% (v/v) and 3.2% (v/v) against S. enterica and L. acidophilus respectively. Acidic PA was evaluated at different concentrations in a simulated poultry digestiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…2016), possess antimicrobial properties, and likely act on the microbiota of the teat to inactivate bacterial enzymes and disrupt cell membranes (Suresh et al . 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2016), possess antimicrobial properties, and likely act on the microbiota of the teat to inactivate bacterial enzymes and disrupt cell membranes (Suresh et al . 2020).…”
Section: Discussionmentioning
confidence: 99%
“…2019; Suresh et al . 2020). These characteristics enable the occurrence of synergistic effects that result in less bacterial resistance compared to that caused by the use of chemicals, such as 2% iodine (Suresh et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…132 Many value-added chemicals such as syringol, ketones, acetol, catechol, levoglucosan, alcohols, and acids can also be obtained from PA. 133 In veterinary and animal production, PA has also been used as a supplement in animals feeding to inhibit growth of enteropathogenic microbes 51 ; to improve digestibility and nutrient absorption 134 ; to promote beneficial effect on the intestinal microbial population. 135 Rattanawut et al 136 observed that a level of 0.4% PA when added to laying duck diet in addition to inhibiting the growth of fecal E. coli, enhanced also productive performance of egg laying ducks. In pig creation, PA facilitates composting of pig manure to reduce NH 3 emissions.…”
Section: Application Of Pamentioning
confidence: 99%